Comparison between modified Dixon MRI techniques, MR spectroscopic relaxometry, and different histologic quantification methods in the assessment of hepatic steatosis. - Kukuk, Guido M; Hittatiya, Kanishka; Sprinkart, Alois M; Eggers, Holger; Gieseke, Jürgen; Block, Wolfgang; Moeller, Philipp; Willinek, Winfried A; Spengler, Ulrich; Trebicka, Jonel; Fischer, Hans-Peter; Schild, Hans H; et al. (European Radiology, 2015)
Objectives: To compare systematically quantitative MRI, MR spectroscopy (MRS), and different histological methods for liver fat quantification in order to identify possible incongruities.Methods: Fifty-nine consecutive patients with liver disorders were examined on a 3 T MRI system. Quantitative MRI was performed using a dual- and a six-echo variant of the modified Dixon (mDixon) sequence, calculating proton density fat fraction (PDFF) maps, in addition to single-voxel MRS. Histological fat quantification included estimation of the percentage of hepatocytes containing fat vesicles as well as semi-automatic quantification (qHisto) using tissue quantification software.Results: In 33 of 59 patients, the hepatic fat fraction was >5% as determined by MRS (maximum 45%, mean 17%). Dual-echo mDixon yielded systematically lower PDFF values than six-echo mDixon (mean difference 1.0%; P < 0.001). Six-echo mDixon correlated excellently with MRS, qHisto, and the estimated percentage of hepatocytes containing fat vesicles (R = 0.984, 0.967, 0.941, respectively, all P < 0.001). Mean values obtained by the estimated percentage of hepatocytes containing fat were higher by a factor of 2.5 in comparison to qHisto. Six-echo mDixon and MRS showed the best agreement with values obtained by qHisto.Conclusions: Six-echo mDixon, MRS, and qHisto provide the most robust and congruent results and are therefore most appropriate for reliable quantification of liver fat.Key Points: • Six-echo mDixon correlates excellently with MRS, qHisto, and the estimated percentage of fat-containing hepatocytes. • Six-echo mDixon, MRS, and qHisto provide the most robust and congruent results. • Dual-echo mDixon yields systematically lower PDFF values than six-echo mDixon. • The percentage of fat-containing hepatocytes is 2.5-fold higher than fat fraction determined by qHisto. • Performance characteristics and systematic differences of the various methods should be considered.